Analysis of brand web positioning assisted by SEMRUSH software - Hachi Mancero, Cristina Belén (mktDESCUBRE; Vol 1 No Especial (2021): Special Edition 4th International Scientific Congress of Administrative and Financial Sciences FADE 2020, 2021)
The article aims to determine the web positioning of a brand taking as a case study the domain www.chevrolet.com since the company has an active presence in digital media, for which the SEMrush web analytics tool was applied, which provides numerical data and web positioning statistics based on website authority metrics, keywords, backlinks, organic and paid advertising, competition, traffic, relevance; With the results obtained, it was determined that the company presents a significant positioning in relation to its competition, especially the company has managed to position itself organically SEO (Search Engine Optimization) without resorting to SEM (Optimization Engine Marketing) positioning in an indispensable way. Its main competition in an organic way is gmauthority.com and its paid competitor is dahlchevroletbuickgm.com, goodyear.com and kia.com, finally the theoretical foundation was established with a scientific approach, it is concluded that the construction of web resposive for computers and mobile devices, establishment of strategies for educational, nutritional and sales content, careful planning of keywords, ad positions, speed of a page and the correct identification of backlinks are essential components in the web positioning of organizations.